Modelagem computacional das interações da integrina VLA-4 humana com ligantes como ferramenta ao planejamento de fármacos - Vasconcelos, Disraeli Cavalcante Araújo (2023)
Integrins are transmembrane receptors that play a critical role in many biological processesof cell migration, which can be therapeutically modulated using integrin antagonists such as peptidomimetic ligands. Thiswork aimedto study the interactionsat the atomic-molecular level of three unprecedentedligands (1592, 2363,and 973) derived from the lead compound BIO-5192 and which are potential inhibitors of α4β1 integrin (VLA-4), as well asthe commercial drugs, initially used for another purpose. For this goal,the binding modes of the compoundswere analyzed and, subsequently, a specific one was selected and submittedto moleculardynamics simulations and free energy calculations by MM/PBSA, in order to evaluate the ligand with the highest affinityto the receptor. PCA analyseswere also applied to the target protein, to verifyits motion modeswhen complexed with different compounds. The results revealed that the 1592 ligand presented a stable behavior at the VLA-4 interaction site, from an average RMSD close to 0.5 nm. PCA analysesalso suggested that the protein receptor had different motion modesin its structure when complexed to 1592, compared to the other compounds. In addition, through the binding free energy calculations, 1592 showed higher affinityto the target in relation to the other studied molecules, through the final ΔGbinding value close to -143 kJ/mol. Therefore, the 1592 ligand represents a possible candidate for a VLA-4 inhibitor drug.Based on virtual screening, molecular dynamics and MM/PBSA methods applied tothecommercial drugs and, through analysis of stability and affinity to the receptor, the drug imatinib representeda potential candidate for VLA-4 integrin antagonist, with an average RMSD close to 0.2 nm and afinal ΔGbinding equalsto approximately -140 kJ/mol. Therefore, the presented results launch new perspectives for the study of different α4β1 antagonists, opening possibilities for drugrepurposingas a tool for drug design.